HUBUNGAN ANTARA KARAKTERISTIK LOKASI CAMERA TRAP DENGAN KEBERHASILAN PEREKAMAN BADAK JAWA (Rhinoceros sondaicus Desmarest 1822) DI TAMAN NASIONAL UJUNG KULON - Intannia Ekanasty; Yanto Santosa; U Mamat Rahmat (Department of Forest Resources Conservation and Ecotourism - IPB University, 2013)
Inventory of the rare javan rhino population keep doing continuously to know the trend of javan rhino population. However, inventory of javan rhino population hard to be done by people because javan rhino very sensitive to human presence. Inventory of javan rhino has improved by using camera trap but not every camera trap effective on capture the javan rhino. One of the problem is the location of camera trap not appropriate with javan rhino movement. Therefore, analizing correlation between characteristic of camera trap site with the success of recording javan rhino is necessary. The objective of this research is to identify the correlation between some of the characteristic of camera trap site which is estimated related to the success of recording javan rhino. The result of this research indicates that distance between camera trap with feces, footprint, human track and topography has correlation with the amount of javan rhino clip. Keywords: camera trap, javan rhino, Ujung Kulon National Park.